Phenology of farmland floral resources reveals seasonal gaps in nectar availability for bumblebees. Issue 7 (9th May 2019) - Timberlake, Thomas P.; Vaughan, Ian P.; Memmott, Jane
Abstract: Floral resources are known to be important in regulating wild pollinator populations and are therefore an important component of agri‐environment and restoration schemes which aim to support pollinators and their associated services. However, the phenology of floral resources is often overlooked in these schemes — a factor which may be limiting their success. Our study characterizes and quantifies the phenology of nectar resources at the whole‐farm scale on replicate farms in Southwestern UK throughout the flowering season. We quantify the corresponding nectar demands of a subset of common wild pollinators (bumblebees) to compare nectar supply and pollinator demand throughout the year, thereby identifying periods of supply‐demand deficit. We record strong seasonal fluctuations in farmland nectar supplies, with two main peaks of nectar production (May and July) and a considerable "June Gap" in between. March and August/September are also periods of low nectar availability. Comparing the phenology of nectar supply with the phenology of bumblebee nectar demand reveals "hunger gaps" during March and much of August/September when supply is unlikely to meet demand. Permanent pasture and woodland produced the greatest share of farmland nectar because of their large area; however, linear features such as hedgerows and field margins provided the greatest nectar per unit area. Fifty percent of total nectar was supplied by just three species ( Allium ursinum, Cirsium arvense and Trifolium repens ), but some less productive species (e.g. Hedera helix and Taraxacum agg.) were important in ensuring phenological continuity of nectar supply. Synthesis and applications . By comparing the phenology of farmland nectar supply with the phenology of pollinator demand, we demonstrate that the timing of nectar supply may be as important as total nectar production in limiting farmland pollinator populations. Considering phenology in the design of agri‐environment or restoration schemes is therefore likely to improve their suitability for pollinators. Plant species which flower during periods of resource deficit (early spring and late summer) should be prioritized in schemes which aim to conserve or restore pollinator populations. Maintaining a range of semi‐natural habitats with complementary flowering phenologies (e.g. woodland, hedgerows and field margins) will ensure a more continuous supply of nectar on farmland, thereby supporting pollinators for their entire flight season. Abstract : By comparing the phenology of farmland nectar supply with the phenology of pollinator demand, we demonstrate that the timing of nectar supply may be as important as total nectar production in limiting farmland pollinator populations. Considering phenology in the design of agri‐environment or restoration schemes is therefore likely to improve their suitability for pollinators. Plant species which flower during periods of resource deficit (early spring and late summer) should be prioritized in schemes which aim to conserve or restore pollinator populations. Maintaining a range of semi‐natural habitats with complementary flowering phenologies (e.g. woodland, hedgerows and field margins) will ensure a more continuous supply of nectar on farmland, thereby supporting pollinators for their entire flight season.